A Consistent Lack of Consistency in Defining the Acute and Chronic Phases of Peyronie's Disease: A Review of the Contemporary Literature. (1st October 2022) - Piraino, Javier; Chaudhary, Hira; Ames, Kyle; Okoye, Frederick; Sterling, Matthew; Clavell-Hernandez, Jonathan; Levine, Laurence; Ziegelmann, Matthew J
Abstract: Introduction: Treatment recommendations for Peyronie's Disease (PD) differ based on whether a patient is in the acute/active versus chronic/stable phase of the disease, yet there are no agreed upon criteria for defining these clinical entities. Objectives: To review the criteria used to define acute and chronic phase PD in modern PD intervention studies Methods: We performed a search engine review to identify indexed publications for PD intervention studies and review articles / meta-analyses from the year 2011-2020. Outcomes results were catalogued and summarized across articles. As a result of the substantial heterogeneity of outcome measures and follow-up intervals, meta-analytic techniques were not applied to the data analysis. Results: We identified a total of 104 studies that met inclusion criteria and had available information for review (n = 79 primary intervention studies; n = 25 review articles/meta-analyses/guidelines). Among the queried studies, we were unable to identify a consensus with respect to the criteria used to define acute and chronic phases of PD. 33% of primary intervention studies did not specifically define their criteria for acute and chronic phase PD, despite referencing these populations as part of the inclusion criteria in many instances. Studies used heterogenous criteria including total symptom duration, duration of "stable" symptoms, and presence/absence of pain. Conclusion: Due to varying definitions across the literature, we were unable to create a standardized definition of acute and chronic phase Peyronie's in terms of time. Our findings emphasize the need for greater consensus in defining the treatment cohorts with future studies that assess treatment for men with PD.